2021
DOI: 10.1016/j.celrep.2021.109411
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin in the anterior cingulate cortex attenuates neuropathic pain and emotional anxiety by inhibiting presynaptic long-term potentiation

Abstract: Oxytocin in the anterior cingulate cortex attenuates neuropathic pain and emotional anxiety by inhibiting presynaptic long-term potentiation Graphical abstract Highlights d Oxytocin microinjected into ACC attenuates injury-related pain and anxiety responses d Oxytocin blocks the maintenance of pre-LTP, but not post-LTP d Oxytocin depolarizes the interneurons and decreases the ratio of E/I transmission d Activation of PVN-ACC pathway blocks pre-LTP and has analgesic and anxiolytic effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 51 publications
(65 reference statements)
1
60
0
Order By: Relevance
“…In this study, the unaltered LTD suggested that LTD in ACC is not involved in chronic pain in PD mice. Presynaptic synaptic plasticity has been identified as playing an important role in chronic pain and anxiety [ 12 , 14 , 25 , 27 ]. Therefore, the presynaptic enhancement of neurotransmitter release in the ACC may contribute to the chronic pain and anxiety in mice of PD model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the unaltered LTD suggested that LTD in ACC is not involved in chronic pain in PD mice. Presynaptic synaptic plasticity has been identified as playing an important role in chronic pain and anxiety [ 12 , 14 , 25 , 27 ]. Therefore, the presynaptic enhancement of neurotransmitter release in the ACC may contribute to the chronic pain and anxiety in mice of PD model.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous EPSCs (sEPSCs) were recorded with the K-gluconate internal solution and holding − 60 mV. Picrotoxin (100 µM) was always present to block GABA A receptor-mediated inhibitory synaptic currents in all experiments [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most of these brain regions are consistent with the BOLD signals increased brain areas in our study. In addition, oxytocin (mainly produced in the PVN) in the anterior cingulate cortex attenuates neuropathic pain and emotional anxiety (Li et al, 2021), revealing that the PVN and Cg have structural or functional connections. Taking the PVN as the seed, it was found that the functional connectivity (FC) between the PVN and the olfactory nucleus, the Cg, the PVT, the PAG, the motor cortex, the caudateputamen, and hippocampus increased after CNO injection (Figure 1D; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Chronic social defeat stress has been reported to decrease expression of oxytocin receptor mRNA in the ACC, inducing anxiety-related behaviors. Oxytocin injection into the ACC has been shown to attenuate nociceptive responses and anxiety-related behavior in animals with neuropathic pain by selectively blocking the maintenance of presynaptic long-term potentiation (LTP) but not postsynaptic LTP [ 112 ]. In humans, intranasal oxytocin has been shown to reduce activation of the dorsal part of the ACC in response to fearful faces in men, while intranasal oxytocin increased ACC activation in women [ 113 ].…”
Section: Stress Responses and Oxytocinmentioning
confidence: 99%